2019
DOI: 10.3389/fmicb.2019.02036
|View full text |Cite
|
Sign up to set email alerts
|

Aedes spp. and Their Microbiota: A Review

Abstract: Aedes spp. are a major public health concern due to their ability to be efficient vectors of dengue, Chikungunya, Zika, and other arboviruses. With limited vaccines available and no effective therapeutic treatments against arboviruses, the control of Aedes spp. populations is currently the only strategy to prevent disease transmission. Host-associated microbes (i.e., microbiota) recently emerged as a promising field to be explored for novel environmentally friendly vector control strategies. In particular, gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
169
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(189 citation statements)
references
References 219 publications
(335 reference statements)
11
169
2
7
Order By: Relevance
“…Similarly, current research continues to elucidate interactions among mosquitoes, their endogenous microbiota, and other pathogens they transmit. In A. aegypti, the microbiota in the mosquito has been reported to influence the susceptibility to infection to arboviruses [13,15,16]. For example, DENV replication has been reported to be affected by gut bacteria [17,18] which exert antiviral activity through mechanisms not completely understood [13,[19][20][21], but that may be indirectly associated to innate antiviral responses and antimicrobial peptides by the gut microbiota [17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, current research continues to elucidate interactions among mosquitoes, their endogenous microbiota, and other pathogens they transmit. In A. aegypti, the microbiota in the mosquito has been reported to influence the susceptibility to infection to arboviruses [13,15,16]. For example, DENV replication has been reported to be affected by gut bacteria [17,18] which exert antiviral activity through mechanisms not completely understood [13,[19][20][21], but that may be indirectly associated to innate antiviral responses and antimicrobial peptides by the gut microbiota [17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of therapeutic treatments and widely available vaccines, control of mosquito population is the most efficient way to prevent arboviral diseases [13]. Mosquitoes are holometabolous insects, whose life cycle goes through four separate stages, including eggs, larva, and pupa in an aquatic habitat and a subaerial adult stage.…”
Section: Introductionmentioning
confidence: 99%
“…Although only the females with anthropophilic blood feeding habit can transmit arboviruses, reducing the population of mosquito on the juvenile stages will decrease the number of adults and subsequently lower the transmission chances. The conventional control strategies, including the use of insecticide and environmental sanitation, are facing challenges due to their sustainability and organizational complexity [13, 14]. In light of the holobiont concept, mosquito-associated microbial communities play an important role in host biology, which may provide new strategies for mosquito control [15].…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes have a resident bacterial gut microbiota that is fundamental for several physiological processes such as larval growth, blood digestion, and immune function [1][2][3], making gut bacteria a prospective avenue for reducing vector competence [4]. For this reason, a multitude of studies have described microbial gut communities of mosquitoes from relevant medical genera (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aedes, Anopheles, and Culex), in different settings (labreared or eld-collected), and in different physiological contexts (e.g. blood-fed, virus-or parasite-infected) (reviewed in [1,2,5]). These studies have demonstrated the taxonomic diversity of bacteria present in mosquito gut tissues, even at the intraspeci c level.…”
Section: Introductionmentioning
confidence: 99%